Hakikat Kepemimpinan Transformasional - Bambang Wiyono (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2019)
The era of globalization marked by the rapid progress in the field of information and technology, can enable major changes in various aspects of human life, all of political, economic, social, cultural, and others. Likewise, changes in organizations both in organizations engaged in social and commercial fields. This condition requires leaders to have adaptive leadership behaviors and can anticipate these changes. Transformational leadership with a variety of indicators that are owned, is seen as capable of carrying out a transforming visionary in the face of various changes, so that the organization can realize its vision into reality.